HBM4EU at a glance - Alvito, Paula (2022)
HBM4EU is a joint effort of 30 countries, the European Environment Agency and the European Commission, co-funded under Horizon 2020. The initiative is coordinating and advancing human biomonitoring in Europe. HBM4EU is generating evidence of the actual exposure of citizens to chemicals and the possible health effects in order to support policy making. The HBM4EU initiative represents a novel collaboration between scientists and chemical risk assessors and risk managers, including several Commission services, EU agencies and representatives for the national level. The project has built bridges between the research and policy worlds in order to deliver benefits to society in terms of enhanced chemical safety.